Peran Media Sosial Instagram (IG) Sebagai Media Promosi di D'Shopia Florist Bali - Sedaniati, Ni Made Sri; Sekarti, Ni Ketut; Adi, Ida Ayu Sri Puspa (Program Studi Manajemen Divisi Kamar, 2023)
Instagram (IG) has become one of the most widely used social media platforms for promotional purposes due to its various features. Businesses in the florist industry, such as D'Sophia Florist Bali, also utilize Instagram (IG) as a promotional tool. This research aims to understand the role of Instagramas a promotional medium for D'Sophia Florist Bali. The study adopts a quantitative approach in collecting and analyzing data. The instrument used is a questionnaire involving 50 respondents who are followers of D'Sophia Florist Bali on Instagram (IG). The questionnaire consists of 10 structured statements regarding 5 online promotion indicators, with responses divided into 5 scales. The research findings show that two indicators, namely advertising and sales promotion, have lower scores which is indicating a less effective role. On the other hand, three indicators such as public relations, direct marketing, and personal selling, have good scores, which is indicating their effective role. This research provides a deeper understanding of the promotion indicators that influence the promotional activities of D'Sophia Florist Bali. The implication of these findings is the need for D'Sophia Florist Bali to enhance their promotional activities conducted through Instagram (IG). Keywords: Instagram (IG), promotion, florist